Adapted Rumen Microorganisms (ARM) for feedlot cattle - Jack G. Riley; K.K. Bolsen; D.L. Good (Kansas Agricultural Experiment Station Research Reports, 1973)
Two trials using 200 mixed breed steers were conducted to determine effects of 0,3, 6, or 12-ounce drenches of Adapted Rumen Microorganisms (ARM) on subsequent feedlot performance. An 85 percent concentrate ration was fed for 90-days before drenching with ARM. Steers receiving the 12-ounce treatment in trial gained 14.4 pounds more per head during the next 60-day feeding period. The 3 and 6-ounce treatments were less beneficial . The 12-ounce treatment in trial 2 produced a highly significant (P<.01) 15% increase in rate of gain and a 12.5% increase in efficiency compared with the control group.
Keywords: Cattlemen' s Day; 1973; Report of progress (Kansas State University. Agricultural Experiment Station); 568; Beef; Feedlot; Adapted Rumen Microorganisms (ARM); Gain